In Vitro and In Silico Antioxidant Activity of Hydrazones and Semicarbazones Derived from Aldehydes Found in Essential Oils - Leandro G. Gutierrez; Carla M. Ormachea; Ana P. Reinick; Vanina A. Guntero; Cristián A. Ferretti (Chemistry Proceedings)
The aim of this study was to investigate the in vitro and in silico antioxidant properties of four hydrazones and semicarbazones derived from vanillin and cinnamaldehyde, aromatic aldehydes found in essential oils. They were synthesized by condensation of these aldehydes with the corresponding phenylhydrazine and semicarbazide in good yields. The antioxidant properties of the target molecules were determined using the Reducing Power assay (RP) and the hydrogen peroxide scavenging method (HP), and the results were compared with thermodynamic descriptors obtained from theoretical calculations using the DFT method. The target molecules were shown to be highly active for the total antioxidant assay and the results of theoretical calculations were consistent with the antioxidant activity observed experimentally, making them a useful tool to understand the mechanism of action. This would also allow theoretical tests of new antioxidant compounds to be carried out in a predictive manner.